2018
DOI: 10.30880/ijie.2018.10.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Measures to Mitigate Causative Factors of Budget Overrun in Malaysian Building Projects

Abstract: Completion of a construction within planned budget is one of the main criteria of project success. However, budget overrun has become a recurring phenomenon in construction industry, which can result in multiple negative effects such as loss of economy, disputes among construction stakeholders, project abandonment, and drop in construction activities. This study aims to identify factors causing budget overrun in Malaysian Building projects and then to establish mitigation measures for the identified significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
0
13
0
3
Order By: Relevance
“…Proprietors' monetary concerns are another cause of time overrun. Authors in [19] reported that www.etasr.com Shaikh: Financial Mismanagement: A Leading Cause of Time and Cost Overrun in Mega Construction … from consultant's opinion, unskilled or lack of management and the dearth of expert's acquaintance and skills were the main reasons for time and price overrun.…”
Section: A Causes Of Constructing Project's Time Overrunmentioning
confidence: 99%
See 1 more Smart Citation
“…Proprietors' monetary concerns are another cause of time overrun. Authors in [19] reported that www.etasr.com Shaikh: Financial Mismanagement: A Leading Cause of Time and Cost Overrun in Mega Construction … from consultant's opinion, unskilled or lack of management and the dearth of expert's acquaintance and skills were the main reasons for time and price overrun.…”
Section: A Causes Of Constructing Project's Time Overrunmentioning
confidence: 99%
“…Authors in [8,19,20] reported the following components in cost surplus: design modifications, unskilled and unfinished preparation, doubtful climate conditions, and abnormality and deviation in the cost of project resources. In addition to this, a listing of serious factors like incomplete design at the tendering phase, design alterations at the request of the proprietor, lack of money for the setting up and supervising at the beginning after the contract signing, defective besmirch and location settings, alterations made during construction, transportation charges owing to place locality, and lack of cost information at the development stage.…”
Section: B Effects Of Construction Project's Cost Overrunmentioning
confidence: 99%
“…This could raise a problem with the client who requires a form of guarantee that all specifications have been met [33]. Hence, when looking for a project input, the clients can found it difficult to sufficiently explain and understand the schedule and drawings for the project; this may lead the owners to work with other parties in order to:…”
Section: Literature Reviewmentioning
confidence: 99%
“…These strategies contain customer's behavior and evacuation scenarios, which can be conducted by the BIM as an initial point for producing these scenarios. Moreover, the facilities which their execution prerequisites are more serious, the initial asset in a BIM can be beneficial because it gives a precise three dimensional model [33].…”
Section: D) Simulate Operations For Facilitiesmentioning
confidence: 99%
“…Input components will affect the stability of the system. Hence to maintain the stability of the systems inputs have to be monitored in a regular manner [15,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%